Soluciones casi automorficas compactas de ecuaciones de evolución casi automórficas en espacios de Banach - Angelats Ormeno, Fernando Alexander (2023)
In the present work, sufficient conditions are determined to guarantee that a weak_x000D_ solution of a almost automorphic evolution equation is compact almost automorphic. In_x000D_ order to reach the established objective, the tools of functional analysis and the theory_x000D_ of semigroups of operators have been used, likewise, some important properties of almost_x000D_ automorphic functions have been investigated and developed. In addition, two application_x000D_ examples have been shown where the established conditions are verified in detail